2003
DOI: 10.1038/sj.bmt.1703778
|View full text |Cite
|
Sign up to set email alerts
|

Patients with acute lymphoblastic leukaemia allografted with a matched unrelated donor may have a lower survival with a peripheral blood stem cell graft compared to bone marrow

Abstract: Summary:We analysed data for 213 patients with ALL and AML who received either peripheral blood stem cells (PBSC) (n ¼ 74) or bone marrow (BM) (n ¼ 139) from an HLAmatched unrelated donor (EBMT acute leukaemia registry; January 1994 to January 1999). The two groups of patients (by cell source) were comparable with respect to age, sex, disease status, year at transplant and graft T cell depletion. Engraftment was achieved in about 90% regardless of stem cell source or leukaemia type. Kinetics of neutrophil and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
3
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 27 publications
3
29
3
1
Order By: Relevance
“…In a retrospective study by Champlin et al 22 through the International Bone Marrow Transplant Registry (IBMTR)/European Bone Marrow Transplant Registry (EBMTR) of 112 adult ALL patients (38 PBSC vs 74 BM), there was no difference in relapse between graft sources, but improved leukemia-free survival (LFS) was shown in CR2 patients receiving PBSC (P ¼ 0.03). This report is contrasted by the Garderet et al 23 analysis through the Acute Leukemia Working Body of the EBMTR, which reported a trend toward greater relapse in 102 ALL patients receiving PBSC (n ¼ 36) than BM (n ¼ 66) (47 vs 39%, P ¼ 0.17) and lower LFS/OS in the PBSC group (P ¼ 0.04). Although there was no significant difference in relapse in either of these analyses between PBSC and BM, and contrasting results regarding LFS, it remains unclear whether PBSC alter the relapse risk or LFS, when compared with BM in ALL.…”
Section: Discussioncontrasting
confidence: 51%
“…In a retrospective study by Champlin et al 22 through the International Bone Marrow Transplant Registry (IBMTR)/European Bone Marrow Transplant Registry (EBMTR) of 112 adult ALL patients (38 PBSC vs 74 BM), there was no difference in relapse between graft sources, but improved leukemia-free survival (LFS) was shown in CR2 patients receiving PBSC (P ¼ 0.03). This report is contrasted by the Garderet et al 23 analysis through the Acute Leukemia Working Body of the EBMTR, which reported a trend toward greater relapse in 102 ALL patients receiving PBSC (n ¼ 36) than BM (n ¼ 66) (47 vs 39%, P ¼ 0.17) and lower LFS/OS in the PBSC group (P ¼ 0.04). Although there was no significant difference in relapse in either of these analyses between PBSC and BM, and contrasting results regarding LFS, it remains unclear whether PBSC alter the relapse risk or LFS, when compared with BM in ALL.…”
Section: Discussioncontrasting
confidence: 51%
“…23 In another non-randomized study of patients with acute leukemias, lower survival was noted in ALL patients with PSCs compared with bone marrow. 24 Unlike other studies, the incidence of acute GVHD was higher in ALL patients who received PSCs.…”
Section: Discussioncontrasting
confidence: 50%
“…by guest www.bloodjournal.org From nonablative than ablative patients received G-PBMCs, previous studies have failed to show consistent differences in outcome between unrelated G-PBMCs and marrow grafts. [31][32][33][34][35] Despite higher frequencies of adverse risk factors, nonablative patients experienced significantly less posttransplantation grade IV toxicity as assessed by NCI-CTC. Individual toxicities for which differences were seen included hematologic, hemorrhagic, infectious, gastrointestinal, hepatic, metabolic, and grades III to IV acute GVHD events.…”
Section: Discussionmentioning
confidence: 99%